ASPEK HUKUM PENGATURAN DAN PENGAWASAN PERBANKAN SYARIAH OLEH OTORITAS JASA KEUANGAN - Nur Sania Dasopang (Indonesian Journal of Thousand Literacies, 2023)
The financial services authority is an institution established under lawa No. 21 of 2011. This institution was established to carry out integrated supervision of the financial services industry. Juridically according to the provisions of article no. 1 of the OJK Law is an independen institution and free from interfence from other parties thatr has the function, duties, powers, supervision, examination, and supervision as referred to in this law. As the function of OJK  its to supervise the implementation of the products Islamic banking and other Islamic financial institutions, then what are the main vision and mission  of the establishment of the OJK and the results of OJK